2018
DOI: 10.4314/gmj.v52i3.2
|View full text |Cite
|
Sign up to set email alerts
|

Students’ perceptions of the learning environment in two Nigerian medical schools offering different curricula

Abstract: Objective: Compare the results of administering the DREEM questionnaire in two Nigerian medical schools offering traditional and student-centred curricular respectively, to identify any differences in the learning environment and appreciate advantages of the more modern curriculum.Methods: A survey design was used. Data was analysed using the DREEM scoring rubric. The independent t-test was used to compare results. Setting: The DREEM questionnaire was administered to final year medical students at two particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 26 publications
0
10
0
1
Order By: Relevance
“…On the other hand a study conducted in Nigeria to compare the perception of students on the educational environment in two Nigerian medical schools offering traditional and student-centered curricula, revealed that the older students in the teacher centered environment showed more positive perception of the educational environment than the younger students in the student centered curricula [ 16 , 19 , 23 ]. This difference might be because of the difference in the study participants of the two Nigerian medical schools.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand a study conducted in Nigeria to compare the perception of students on the educational environment in two Nigerian medical schools offering traditional and student-centered curricula, revealed that the older students in the teacher centered environment showed more positive perception of the educational environment than the younger students in the student centered curricula [ 16 , 19 , 23 ]. This difference might be because of the difference in the study participants of the two Nigerian medical schools.…”
Section: Discussionmentioning
confidence: 99%
“…The DREEM has a maximum score of 200, representing an ideal educational environment [ 5 , 7 , 16 18 ]. Individual items of the DREEM scores were classified as positive if the mean value is greater than 2 and negative if mean value is 2 or below [ 5 , 16 ]. Subscales of DREEM scores were described using mean values.…”
Section: Methodsmentioning
confidence: 99%
“…The assessment of the learning environment in the nursing student participants of this study is more positive than negative, as in many studies where this tool was used [15,35,54,[60][61][62][63][64][65][66][67][68]. So far, only one study has been conducted that provides researchers with insight into the differences between personal and online teaching.…”
Section: Discussionmentioning
confidence: 99%
“…Respondents are presented with a statement and asked to select a response. Items 4,8,9,17,25,35,39,48 and 50 are negatively worded and these require recording prior to calculating the total and subscale scores. The DREEM tool's Cronbach alpha was 0.863.…”
Section: Dreemmentioning
confidence: 99%